Race, Africana communication, and criminal justice reform: a reflexive and intersectional analysis of adaptive vitality - Johnson, Detra D.; Lovett, Marilyn; Lipschultz, Jeremy Harris (Lexington Books, 2024)
"This volume discusses issues and themes surrounding communication, social media, online protests, policing, criminal justice reform, and freedom of speech. The contributors offer analyses embracing social justice in the areas of educational and criminal justice reform, as well as communication principles grounded in Africana praxis"--